Phosphohistone H3 as the standard of immunohistochemical study in the assessment of differentiation level of oropharyngeal zone squamous cell carcinomas - А. V. Lysak; О. О. Dyadyk (Zaporozhye State Medical University, 2016)
Verification and grading of tumors of oropharyngeal areas, determination of their malignancy potential remain an urgent problem as well as diagnosis and prognosis today. The aim of our research was to determine the proliferative index (Ki67), and the actual number of mitoses (pHH3) and to compare them with the morphological (histological) picture. Materials and methods. 121 cases of flat-cell cancer using monoclonal and polyclonal antibodies were analyzed in this article. The dependence between proliferation index (Ki67), the number of mitoses (pHH3) and morphological criteria was investigated. The assessment of differentiation level with Anneroth et al. 1987 u. Bryne et al. 1992 technique was used. Results and discussion. We received the following distribution by three main groups after re-assessment of the level of differentiation. Group №1 which contains G1 tumors includes 22 patients, group №2 G2 of 45 patients and №3 G3 of 54 patients. All three groups were morphologically described. The groups were evaluated on the results of IHC markers Ki67 and pHH3 further. Statistically the significant difference between groups (p <0,001 by Kruskal-Wallis test for all indicators) was found when comparing indicators Ki-67, pHH3. So with the decrease of Me level the differentiation of KI67 significantly (p <0.05) increases and the increase of pHH3 reflects the growing of tumors malignancy degree. Conclusions. The relationship between Ki67, pHH3 and the level of differentiation of squamous cell carcinomas of oropharyngeal area has been statistically proved. The opportunity to use pHH3 marker as a reliable criterion for assessing the level of differentiation of tumors, including squamous cell carcinomas which are difficult to be diagnosed, was set as a result of our work.